REVITALISASI HADIS QUDSI PADA GRUP HADITS QUDSI MUSLIMAH - Irfan Yuhadi; Nurul Budi Murtini (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
Among the implications of the rapid development of information technology is a shift in moral value in society, both on a micro and macro scale. So that a religious approach is needed through hadith qudsi education to overcome this. Hadith qudsi give many motivations to humans to do good and stay away from various bad things. Therefore, it is necessary to revitalize hadith qudsi for the Indonesian muslim community as an effort to increase the religiosity of the community. The purpuse of this research is to analyze and find the revitalization of hadith qudsi in Indonesian muslim society. The approach used in this research is a mixed method with a total sample of 150 people teken using a simple random sampling technique from the Hadith Qudsi group participant spread across 45 city in Indonesia. The result of this research indicates that: the majority of the Indonesian muslims do not know in detail about hadith qudsi. The revitalization of hadith qudsi is carried out by massively educating hadith qudsi to the Indonesian muslim community through social media networks. Hadith qudsi education though social media networks has a significant effect on increasing the religiosity of the Indonesian muslim community. The magnitude of the influence of hadith qudsi education on people’s religiosity is 57%.